2022
DOI: 10.3390/ijerph19148676
|View full text |Cite
|
Sign up to set email alerts
|

Home Oral Care with Biomimetic Hydroxyapatite vs. Conventional Fluoridated Toothpaste for the Remineralization and Desensitizing of White Spot Lesions: Randomized Clinical Trial

Abstract: Introduction: Biomimetic hydroxyapatite-based toothpastes have been investigated in recent years for their remineralizing activity on dental surfaces. The aim of the present study was to evaluate the efficacy of toothpaste containing biomimetic hydroxyapatite versus a 1450 pppm fluoride one in promoting the remineralization and desensitization of white spot lesions. Methods: 40 patients were randomly assigned to two different domiciliary oral hygiene treatments: toothpaste containing 1450 ppm of fluoride (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Additionally, the protective efects of these fuoride varnishes were evaluated without mechanical action, which can be considered another limitation of this study. Notably, a recent study showed that the use of a toothpaste containing hydroxyapatite could be a more reliable method for the domiciliary management of WSLs than the use of conventional fuoride toothpaste [37]. It might be interesting to compare the efcacy of toothpaste containing biomimetic hydroxyapatite with that of the two varnishes investigated in this study.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the protective efects of these fuoride varnishes were evaluated without mechanical action, which can be considered another limitation of this study. Notably, a recent study showed that the use of a toothpaste containing hydroxyapatite could be a more reliable method for the domiciliary management of WSLs than the use of conventional fuoride toothpaste [37]. It might be interesting to compare the efcacy of toothpaste containing biomimetic hydroxyapatite with that of the two varnishes investigated in this study.…”
Section: Discussionmentioning
confidence: 94%
“…After our search was completed, 4 additional studies appeared in the literature that were not included in this qualitative or quantitative synthesis [ 78 , 79 , 80 , 81 ]. These studies were consistent with HAP in reducing dentin hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride-free prophylactic systems have been investigated in the last decade. It has been shown that they can be as efficient as fluoride-containing systems to prevent dental caries [ 8 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Thus, they may present a viable alternative to fluoride-containing agents in oral care.…”
Section: Discussionmentioning
confidence: 99%